2018
DOI: 10.11158/saa.23.3.4
|View full text |Cite
|
Sign up to set email alerts
|

Leprosis mite and other mite species (Acari) associated to orange groves in Brazilian Central Amazon

Abstract: The citrus leprosis mite, Brevipalpus yothersi Baker, is not considered to cause major damage to orange trees in the Brazilian Amazonas state. However, little is known about the diversity of plant mites and about mite damage to plants in this state of northern Brazil. The objective of the present study was to evaluate the level of occurrence of the leprosis mite in this region and the diversity and prevailing population levels of associated mites in unsprayed orange groves of the surroundings of Manaus, Amazon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 19 publications
1
8
0
1
Order By: Relevance
“…Amblyseius aerialis has been reported in the Amazon region in association with Citrus sp. in the states of Amapá (Mineiro et al 2009) and Amazonas (Bobot et al 2011;Ferreira et al 2018). This predator has also been found on other plants in the Amazon, such as Hevea spp.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Amblyseius aerialis has been reported in the Amazon region in association with Citrus sp. in the states of Amapá (Mineiro et al 2009) and Amazonas (Bobot et al 2011;Ferreira et al 2018). This predator has also been found on other plants in the Amazon, such as Hevea spp.…”
Section: Discussionmentioning
confidence: 79%
“…in the states of Acre, Amazonas, and Rondônia (Nuvoloni et (Demite et al 2018). In Amazonas, A. aerialis was reported as the most abundant predator with potential for control of the leprosy mite, B. yothersi (Ferreira et al 2018). This phytoseiid, with E. concordis and I. zuluagai, may also be potential candidates for the biological control of S. hindustanicus, and complementary studies should be conducted to assess its predatory impact on this pest.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted in Manaus region, of the Brazilian Amazonia, Bobot et al (2011) reported ten species of phytophagous mites from citrus plants, belonging to the families Eriophyidae, Tenuipalpidae and Tetranychidae. In a more recent study conducted in the same region, six species of phytophagous mites were reported by Ferreira et al (2018), all of which also reported by Bobot et al (2011).…”
Section: Introductionmentioning
confidence: 80%
“…Several species of predatory mites were collected in the study conducted by Ferreira et al (2018), including eight phytoseiid species. The most numerous species were Amblyseius aerialis Muma and Iphiseiodes zuluagai Denmark & Muma, corroborating the results of Bobot et al (2011).…”
Section: Introductionmentioning
confidence: 99%
“…To date, the only cunaxid species reported from the Amazonic biome is A. huyssteeni (Ferreira, Krug, Garcia & Moraes, 2018). This paper presents the first survey of cunaxids from the Amazonic biome and describes the male of Scutopalus tomentosus and a new species of Armascirus collected from Cocos nucifera from the state of Pará, Brazil.…”
Section: Introductionmentioning
confidence: 99%